Gestión empresarial y el desarrollo de las micro y pequeñas empresas de la ciudad de Iquitos 2021 - Rios Babilonia, Walter Jaime (2022)
The research problem identified in this work is that there is a lack of good management by managers, which leads to a lack of growth for companies in the district of Iquitos. This situation is due to a poor economy, inefficiency of the company to reach its goals, a lack of continuous improvement, the almost non-existent development of the market, the lack of expansion towards other cities, non-diversified goods and services, as well as the financial difficulties. SMEs lack an adequate financial capital structure, defined by a balance sheet that clearly defines their assets, liabilities and assets; as a result, they lack the means or resources to secure investments. Small or medium-sized companies usually have an inadequate structure for investment, having little or no contribution to the company from fixed assets. Working capital deficiencies, or shortfalls in current assets, may be due to a lack of cash, insufficient assets leading to unsatisfied demand, or other balance sheet deficiencies. The same can happen with the accounting circulating capital, that is, the current assets minus the current liabilities, it is insufficient to fulfill the obligations with its suppliers in the same way. The present study combines the methodological conditions of an applied research with the reasoning that the knowledge of administrative sciences will be applied to management and business development in the district of Iquitos.